The presence of peripheral arthritis delays spinal radiographic progression in ankylosing spondylitis: Observation Study of the Korean Spondyloarthropathy Registry - Kim, T.-J.; Lee, S.; Joo, K. B.; Park, D.-J.; Park, Y.-W.; Lee, S.-S.; Kim, T.-H. (Rheumatology (Oxford, England), 2014)
The aim of this study was to determine whether the presence of peripheral arthritis can affect radiographic structural damage in patients with AS. A total of 915 subjects comprising 363 patients with a history of peripheral arthritis and 552 patients without a history of peripheral arthritis obtained from the Observation Study of the Korean SpA Registry (OSKAR) were analysed looking at the relationship of peripheral arthritis history in a cross-sectional survey as well as the radiographic damage score according to the presence or absence of peripheral arthritis. Radiographs and clinical information were available for 501 subjects (205 peripheral arthritis patients and 296 without peripheral arthritis) at a mean follow-up of 2.7 years. The modified Stoke AS Spinal Score (mSASSS) was examined by two experienced radiologists to validate the results. Reliability was evaluated using the intraclass correlation coefficient for each radiograph. The agreement between the two readers regarding the mSASSS was good. On simple comparison there was a significant difference in the mSASSS between patients with a history of peripheral arthritis and those without [mean 14.62 (s.e.m. 0.83) vs 18.78 (0.79), P < 0.001]. The mSASSS change was stratified according to the presence or absence of peripheral arthritis at baseline. After adjusting for multiple comparisons by Bonferroni correction, the patients with peripheral arthritis had less mSASSS change than those without peripheral arthritis [3.08 (s.e.m. 0.61) vs 5.18 (0.47), P = 0.008]. The presence of peripheral arthritis delays spinal radiographic progression in AS.